The immune‐related role of BRAF in melanoma - Tomei, Sara (Mol Oncol, 2014)
BACKGROUND: The existence of a dichotomy between immunologically active and quiescent tumor phenotypes has been recently recognized in several types of cancer. The activation of a Th1 type of immune signature has been shown to confer better prognosis and likelihood to respond to immunotherapy. However, whether such dichotomy depends on the genetic make‐up of individual cancers is not known yet. BRAF and NRAS mutations are commonly acquired during melanoma progression. Here we explored the role of BRAF and NRAS mutations in influencing the immune phenotype based on a classification previously identified by our group. METHODS: One‐hundred‐thirteen melanoma metastases underwent microarray analysis and BRAF and NRAS genotyping. Allele‐specific PCR was also performed in order to exclude low‐frequency mutations. RESULTS: Comparison between BRAF and NRAS mutant versus wild type samples identified mostly constituents or regulators of MAPK and related pathways. When testing gene lists discriminative of BRAF, NRAS and MAPK alterations, we found that 112 BRAF‐specific transcripts were able to distinguish the two immune‐related phenotypes already described in melanoma, with the poor phenotype associated mostly with BRAF mutation. Noteworthy, such association was stronger in samples displaying low BRAF mRNA expression. However, when testing NRAS mutations, we were not able to find the same association. CONCLUSION: This study suggests that BRAF mutation‐related specific transcripts associate with a poor phenotype in melanoma and provide a nest for further investigation.